Science writing in the real world - Mike Mentis (Forest Ecosystems, 2014)
The objective of this contribution is to consider guides to technical writing. Since the professional writes what he does and does what he writes, guides to how you execute the one relate to how you perform the other, so this article is about more than just writing. While there is need for idiosyncrasy and individualism, there are some rules. Documents must have an explicit purpose stated at the outset. By their nature, documents in the applied sciences and business address real-world problems, but elsewhere activity may be laissez faire for which the cost-effectiveness in yielding innovations is contestable. A hallmark of written science and technology is that every statement is capable of being tested and capable of being shown to be wrong, and that methods yield repeatable results. Caution should be observed in requiring authoritative referencing for every notion, partly because of the unsatisfying infinite regress in searching for ultimate sources, and partly to avoid squashing innovation. It is not only the content of messages that matters, but reliability too. Probability theory must be built into design to assure that strong inference can be drawn from outcomes. Research, business and infrastructure projects must substitute the frequent optimistic ‘everything goes according to plan’ (EGAP) with a more realistic ‘most likely development’ (MLD) and the risks of even that not happening. A cornerstone of science and technology is parsimony. No description, experiment, explanation, hypothesis, idea, instrument, machine, method, model, prediction, statement, technique, test or theory should be more elaborate than necessary to satisfy its purpose. Antifragility – the capacity to survive and benefit from shocks – must be designed into project and organizational structure and function by manipulating such factors as complexity and interdependency to evade failure in a turbulent and unpredictable world. The role of writing is to integrate these issues, and communicate them so that the stakeholders share a vision before, during and after the project.